Tooth Fairy 2 [videorecording (DVD)] - Zamm, Alex; Larry, the Cable Guy; Reiter, Brady; Beute, Erin; Mackey, David; Zazove, Ben; Piddock, Jim, 1956- (20th Century Fox Home Entertainment, 2012)
Larry Guthrie is a fun-loving guy with a serious mission: to win back Brooke, the love of his life. But when Larry upsets a small boy with a loose tooth where Brooke works, he's 'sentenced' to become a real Tooth Fairy. It's tutu times the laughs watching Larry strut his stuff in pink tights and ballet shoes as he tries to restore the boy's faith before Brooke marries the wrong man, and he only has ten days to git-r-done!